P759 Ustekinumab as rescue treatment in therapy-refractory or -intolerant ulcerative colitis. (16th January 2018) - Ochsenkühn, T; Janelidze, S; Tillack, C; Beigel, F
Abstract: Background: Ustekinumab is a monoclonal antibody targeting interleukins-12 and -23, commonly and successfully used in Crohn's disease. Pre-approval trials are on-going and so far no clinical observation data on the use of ustekinumab in ulcerative colitis (UC) is available. AIM: To assess the clinical outcomes achieved with ustekinumab as rescue treatment in therapy-refractory or -intolerant UC. Methods: A retrospective data analysis was performed in 17 UC patients of our tertiary referral center who received ustekinumab between 2016 and 2017 as rescue therapy. All patients were intolerant or refractory to purine-analogues, TNF-antibody therapy, and the anti-integrin vedolizumab. To all patients ustekinumab was provided as a rescue treatment after colectomy had been offered to them as only other option. The primary outcome was achievement of clinical remission at 3 and 6 months. Clinical remission was defined as score of ≤5 points in the modified Truelove and Witts colitis activity index (CAI). Results: A total of 17 UC patients were treated with ustekinumab. All patients (17/17) previously had been steroid-refractory or -dependant and had recently failed all of the following drugs: purine-analogues, anti-TNF-antibodies and anti-integrin-antibodies. Of those, 41% (7/17) had failed infliximab and either golimumab or adalimumab, and 29% (5/17) had also failed i.v. ciclosporine. At the start of the rescue therapy, 65% of patients (11/17) had moderately or severely active disease and 35% (6/17) were in remission, but had intolerable side effects under TNF- or integrin blocking treatment, which had to be stopped. Therefore, the CAI at the start of the therapy ranged between 1 and 11 with a median of 8. All patients received ustekinumab as approved for Crohn's disease (6 mg/kg body weight as an infusion and 90 mg ustekinumab as s.c. injection every 8 weeks). Median follow-up was 27 weeks (range: 15–40). In two patients therapy was stopped due to refractory disease at months 6 and 24 and in 1 patient, therapy was stopped due to drowsiness at week 4. All 3 patients underwent colectomy. Median CAI at 4 weeks was 5 points (range 1–8). Median CAI at 3 months was 4.5 points (range 0–9). Median CAI at 6 months was 2 points (range 0–7). Including the three drop-outs, clinical remission was achieved in 65% (11/17) at 1, 3, and 6 months, whereas only 35% (6/17) of patients were in remission at the start of the study. Conclusions: Ustekinumab was effective as rescue medication in therapy-refractory or -intolerant UC in a large IBD referral center. It seems possible that large ongoing trials will confirm our findings and ustekinumab could become a new therapeutic option for refractory UC.